Resource consumption and patient employability during systemic therapy and biological therapy - L. S. Kruglova; A. A. Hotko (Izdatelstvo OKI, 2021)
An important aspect of the treatment of patients with psoriasis and psoriatic arthritis is the cost of the applied methods of therapy, the costs of the healthcare system associated with the treatment of such patients, and the effect of the disease on the ability to work. The costs of the health care system are the most important component of assessing the use of various methods of therapy and are characterized not only by the financial side, but also by the assessment of the workload of medical organizations and the health care system in general. Research results. During this program, it was found that the use of GIBP is associated with a decrease in the average duration of one hospitalization case: this indicator was 2.07 days, while in patients on other types of therapy it reached an average of 10.01 days. In patients receiving other types of therapy, the average number of hospitalizations in a round-the-clock hospital was significantly higher and amounted to 0.53 compared with the GAI - the indicator corresponded to 0.10. In addition, patients on the BAU were less likely to seek outpatient care and received fewer sick leaves, which were characterized by a shorter duration. Conclusions. The use of GIBP reduces the burden on the dermatological and rheumatological service, reduces the duration of hospitalizations, and significantly improves the socio-economic situation of patients due to a more significant preservation of their ability to work.